Species Diversity of Cotton Insect Pests - Ohnmar Khaing; Praparat Hormchan; Surachate Jamornmarn; Ngarmchuen Ratanadilok; Arunee Wongpiyasatid (Agriculture and Natural Resources, 2002)
Field experiments were conducted at Suwan Farm, Northeastern Thailand during two growing periods of 2000 and 2001 to determine the species diversity and abundance of insect pests of cotton. Randomized Complete Block Design (RCB) was arranged with four replications of sixteen plots of four cotton varieties/lines. Weekly sampling was performed by visual count and pan trap methods. Species diversity of insect pests was analyzed by Shannon-Weaver diversity index. Species abundance of insect pests was computed for each crop together with eight sampling dates. Species ranking was also developed from species abundance. The results showed that insect pests were greatly abundant during the first crop while low diversity indices were observed. During the second crop there was less appearance of insect pest. The total species abundance of all varieties/lines ranged from 10 (cotton spiny bollworm, Earias sp.), to 11,431 (cotton leafhopper, Amrasca biguttula Ishida), in the first crop and from 11 (Earias sp.), to 1,955 (A. biguttula), in the second crop. The ranges of species diversity indices were from 0.27 [Sri Samrong 60 (SR 60)] to 0.62 [Sarid 1 (SD1)], in the first crop and from 0.61 (SR 60) to 0.83 (SD1), in the second crop. A. biguttula was observed to be the dominant species in both crops. Other insect pests with less obvious importance were Thrips palmi, Bemisia tabaci, Aphis gossypi, Megacoelum biseratense and Carpophilus sp. Although total of 28 species found on cotton, only 13-14 insect pests appeared in the cotton field regularly. Two rare species did not occur on some cotton varieties/lines during the second crop.